Kinetic and thermal study of dye adsorption on TiO2 and sequential dye adsorption model for dye sensitized solar cells (DSSC) - Lee, Wee Ping. (2010)
As the site to generate electrons, dye and its attachment process on TiO2 in dye-sensitized solar cells is critical for high cell performance, yet it is not well studied. The aim of this project is to understand the dye adsorption mechanism on TiO2 and investigate the relationship between the dye loading conditions (namely dye soaking time and temperature) to cell photovoltaic performance.